2016
DOI: 10.1097/pec.0000000000000669
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Approach to Minimizing Acute Procedural Pain in the Emergency Department and Beyond

Abstract: In summary, there currently remains a knowledge-to-practice gap in the treatment of children's procedure-related pain. This article has identified multiple age-specific methods to improve the treatment of procedural pain. These simple interventions can improve the care provided to ill and injured children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 74 publications
0
67
0
3
Order By: Relevance
“…Nonpharmacologic methods that are commonly used to reduce the effects of invasive procedures in newborns include breastfeeding (Obeidat & Shuriquie, 2015;Pillai Ridell, et al, 2015;Harrison et al, 2016;Okan et al, 2010;Yilmaz & Arikan, 2011;Shah, Herbozo, Aliwalas, & Shah, 2012;Uga et al, 2008;Marín Gabriel et al, 2013;Aguilar Cordero, Mur Villar, García García, Rodríguez López, & Rizo Baeza, 2014), pacifiers (da Motta & da Cunha, 2015Yilmaz & Arikan, 2011), and sucrose and sweet solutions (Kassab, Anabrees, Harrison, Khriesat, & Chen, 2017;Kassab, Foster, Foureur, & Fowler, 2012;Pillai Riddell et al, 2015;Yilmaz & Arikan, 2011). Other alternatives include music therapy (Marofi, Nikobakht, Badiee, & Golchin, 2015); massage, touching, and positioning (Hartley, Miller, & Gephart, 2015); and nesting, kangaroo care, foetal positioning, and wrapping (Morrow et al, 2010;Prasopkittikun & Tilokskulchai, 2003;Okan et al, 2010;Obeidat & Shuriquie, 2015;Ali, McGrath, & Drendel, 2016;Cong, 2015;Shu et al, 2014). Breastfeeding is reported as effective in reducing pain during minor painful procedures (Chromá & Sikorová, 2012;da Motta & da Cunha, 2015;Obeidat & Shuriquie, 2015;Shah et al, 2012), and it is suggested that it should be used to reduce pain during interventional procedures in newborns (Ali et al, 2016;Reece-Stremtan & Gray, 2016;Shah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonpharmacologic methods that are commonly used to reduce the effects of invasive procedures in newborns include breastfeeding (Obeidat & Shuriquie, 2015;Pillai Ridell, et al, 2015;Harrison et al, 2016;Okan et al, 2010;Yilmaz & Arikan, 2011;Shah, Herbozo, Aliwalas, & Shah, 2012;Uga et al, 2008;Marín Gabriel et al, 2013;Aguilar Cordero, Mur Villar, García García, Rodríguez López, & Rizo Baeza, 2014), pacifiers (da Motta & da Cunha, 2015Yilmaz & Arikan, 2011), and sucrose and sweet solutions (Kassab, Anabrees, Harrison, Khriesat, & Chen, 2017;Kassab, Foster, Foureur, & Fowler, 2012;Pillai Riddell et al, 2015;Yilmaz & Arikan, 2011). Other alternatives include music therapy (Marofi, Nikobakht, Badiee, & Golchin, 2015); massage, touching, and positioning (Hartley, Miller, & Gephart, 2015); and nesting, kangaroo care, foetal positioning, and wrapping (Morrow et al, 2010;Prasopkittikun & Tilokskulchai, 2003;Okan et al, 2010;Obeidat & Shuriquie, 2015;Ali, McGrath, & Drendel, 2016;Cong, 2015;Shu et al, 2014). Breastfeeding is reported as effective in reducing pain during minor painful procedures (Chromá & Sikorová, 2012;da Motta & da Cunha, 2015;Obeidat & Shuriquie, 2015;Shah et al, 2012), and it is suggested that it should be used to reduce pain during interventional procedures in newborns (Ali et al, 2016;Reece-Stremtan & Gray, 2016;Shah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other alternatives include music therapy (Marofi, Nikobakht, Badiee, & Golchin, 2015); massage, touching, and positioning (Hartley, Miller, & Gephart, 2015); and nesting, kangaroo care, foetal positioning, and wrapping (Morrow et al, 2010;Prasopkittikun & Tilokskulchai, 2003;Okan et al, 2010;Obeidat & Shuriquie, 2015;Ali, McGrath, & Drendel, 2016;Cong, 2015;Shu et al, 2014). Breastfeeding is reported as effective in reducing pain during minor painful procedures (Chromá & Sikorová, 2012;da Motta & da Cunha, 2015;Obeidat & Shuriquie, 2015;Shah et al, 2012), and it is suggested that it should be used to reduce pain during interventional procedures in newborns (Ali et al, 2016;Reece-Stremtan & Gray, 2016;Shah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When used appropriately; non-pharmacologic methods can be effective in dulling procedural pain. Non-pharmacologic methods used in children can be categorized in three main groups: supportive methods, cognitive/behavioral methods and physical methods [11][12][13][14]. Supportive methods comprise techniques, such as watching a video, reading a book, family's presence alongside the child during painful procedure; physical methods include touching, giving position, massage, skin stimulation, hot and cold pack application [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Because topical liposomal lidocaine and amethocaine have a faster onset of action, they seem to be more attractive agents than EMLA Ò for use in the ED, where time restraint is often an issue [98].…”
Section: Topical Anestheticsmentioning
confidence: 99%
“…Dose ranges vary in the different protocols published, from as low as 0.05-0.5 ml in newborns to 2 ml given 2 min prior to the procedure and completion of the dose during the procedure if starting with a lower dose, up to a total of 1-2 ml of sucrose 24-33 % per procedure in term infants [97][98][99].…”
Section: Sucrosementioning
confidence: 99%